P096 Pregnancy outcomes in women attending a joint obstetric and rheumatology clinic in a tertiary centre over a 2-year period. (26th April 2021) - David, Trixy; Hum, Ryan Malcolm; Lau, Yen June; Thornber, Sue; Simcox, Louise; Bruce, Ian N; Tower, Clare; Ho, Pauline
Abstract: Background/Aims   The Lupus in Pregnancy Scanning (LIPS) clinic, a joint obstetrics and rheumatology clinic was established in 2010 at Saint Mary's Hospital, Manchester, UK for women with systemic lupus erythematosus (SLE) and other complex rheumatological conditions. We aimed to describe pregnancy outcomes of women attending this clinic to establish a baseline for future changes aimed at improving the service. Methods   Data were collected retrospectively from electronic records of patients who attended the LIPS clinic at least once between 1 st January 2018 and 31 st December 2019. Results   Pregnancy outcomes were available in 105/125 (84%) women (Table ). The median age [inter-quartile range] was 30.6 years [IQR 27.7 - 33.6] and 40 (38%) were of non-Caucasian background. Sixty-one (58%) had a connective tissue disease (CTD) of whom 36 (59%) had SLE. Other rheumatological diagnoses included inflammatory arthritis, primary anti-phospholipid syndrome (APS) and systemic vasculitis. Anti-Ro was found in 32 (31%) and anti-phospholipid antibodies in 25 (24%). During pregnancy, 65 (62%) received aspirin and 40 (38%) had low molecular weight heparin (LMWH). In the antenatal period, 43 (41%) took steroids, 52 (50%) had conventional disease modifying anti-rheumatic drugs and 8 (8%) received biologics. Active disease in the antenatal period was noted in 14 (13%) women. Regarding pregnancy outcomes (Table ), still-births were low (0.95%). The rate of C-sections (45%) and assisted deliveries (19.6%) was comparable to previously published data from similar clinics. Conclusion   In this cohort we report a high live birth rate and comparable rates of assisted delivery to similar cohorts. Infection and post-partum haemorrhage are maternal complications that are common, and reflect the complex clinical presentations and therapeutic regimes in these conditions. Overall this specialist clinic achieves favourable maternal and foetal outcomes in this high-risk population. Disclosure   T. David: None. R. Hum: None. Y. Lau: None. S. Thornber: None. L. Simcox: None. I. Bruce: None. C. Tower: None. P. Ho: None.